Key Experiences of Volunteers in Refugee Aid - Landmann, Helen; Siem, Birte; Fuchs, Birgit; Rohmann, Anette (Journal of immigrant & refugee studies, 2023)
To investigate the specific events and processes that contribute to volunteering in refugee aid, we conducted a qualitative study with volunteers in Germany (N = 220). Participants described in their own words critical incidents that motivated them to volunteer. Content analysis revealed contact with refugees (spatial closeness or conversation), contact with non-refugees (volunteers or xenophobic persons), media experiences (reports about refugees or calls for action), and biographical incidents (own migration or major life changes) as key experiences. The results provide valuable insights into experiences that motivate people to volunteer in refugee aid, which supports integration processes of refugees and asylum-seekers.